Earning Management and the Likelihood of Financial Distress in Banks: Evidence from Pakistani Commercial Banks - Malik, Amina; Din, Shahab Ud; Shafi, Khuram; Zaheer Butt, Babar; Aziz, Haroon (Public Finance Quarterly, 2023)
This research studies the relationship between financial distress (FD) and usage of discretion by employing earning management practices in twenty commercial banks of Pakistan, listed at Pakistan Stock Exchange (PSX). The study utilizes the data spread over from the year 2010 to 2015. Altman Z-Score has been employed to assess financial distress. Further, the value of Z-score has been used for the classification of banks into distressed and non-distressed banks. Moreover, earning management has also been categorized into non-discretionary (NDA) and discretionary accruals (DA). The logistic approach has been used to study the relationship among variables. The findings reveal that banks use non-discretionary and discretionary accruals to manage their financial distress. This research study provides useful insights for investors, auditors and regulators as it identifies usage of specific provisions by management despite strict regulations.